Efficiency of Unloading Time of Fish Catches at Nusantara Sibolga Fishery Port, North Sumatra - Maria Belen Siregar; Lauura Hermala Yunita; Yun Alwi (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Unloading efficiency is the optimal outcome of well-executed, quick unloading activities that avoid wasted time. This research aims to determine the efficiency of unloading fish catches and the factors that influence it at the Sibolga Archipelago Fisheries Port (PPN). This research was carried out at the Archipelago Fisheries Port (PPN) Sibolga, Central Tapanuli Regency, North Sumatra Province, from 19 January to 20 February 2024. The method used in this research was a survey. Then, the sample determination method uses purposive sampling, namely, samples selected according to predetermined criteria; 50 samples were collected using data analysis of demolition time efficiency and multiple linear regression. The variables observed were the ship's size, the number of catches, the number of unloaders, the number of sorters, and the amount of wasted time. The results of this research show that time efficiency is 76%. Then the R-squared value is 0.72, and the multiple R value is 0.84. Furthermore, the calculated F value was 22.665, and the F table was 3.545. It can be concluded that the unloading efficiency at the Sibolga Archipelago Fisheries Port (PPN) is 76%, which is considered efficient